Microbial metabolic efficiency and community stability in high and low fertility soils following wheat residue addition - Liu, Benjuan; Bei, Qicheng; Wang, Xiaojie; Liu, Qi; Hu, Shuijin; Lin, Zhibin; Zhang, Yanhui; Lin, Xingwu; Jin, Haiyang; Hu, Tianlong; Xie, Zubin (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2021)
Soil microbial metabolic efficiency and microbial community stability following the amendment of plant residue to soils are of great importance to the improvement of soil carbon storage and soil fertility. However, heterogeneity of microbial metabolic efficiency and community stability in soils with different fertility defined based on the crop yield, as well as the underlying mechanisms still remains elusive. Here, soils with high and low fertility (HF and LF) were incubated with 13C-labeled wheat residue and analyzed periodically for microbial metabolic quotient and functional bacterial populations using DNA-stable isotope probing technique combined with high-throughput sequencing. Results revealed that soil organic matter (SOM) decomposers following wheat residue amendment were suppressed in HF but stimulated in LF, leading to a higher microbial metabolic efficiency and lower priming effect in HF. This difference in SOM decomposers' responses could be due to that microbes in nutrient- limited LF has to mine recalcitrant SOM for nutrient requirement to support the utilization of wheat residue, the ample nutrients in HF, however, render the microbes to directly utilize wheat residue. Both the resistance (disturbance stability) and resilience (temporal stability) of bacterial community were higher in HF than in LF following disturbance of wheat residue addition. Higher abundance and lower composition variation of wheat residue decomposers in HF than in LF might result in the higher stability of microbial community in HF. The results suggest that plant residue amendment to fertile soils is likely more effective for soil carbon accumulation and soil fertility buildup than to infertile soils, due to higher microbial metabolic efficiency and higher microbial community stability. [Display omitted] •Microbial metabolic efficiency is higher in high fertility soil than in low following the amendment of wheat residue.•SOM decomposers are suppressed in high fertility soil, while they were stimulated in low following wheat residue amendment.•The bacterial community is more stable in high fertility soil than in low fertility soil.•Plant residue amendment to fertile soils is likely more effective for soil fertility buildup.